Meningkatkan Ekonomi Masyarakat Desa Klis Melalui Produk Kreatif Dari Pengolahan Singkong - Ince Wattimury; Fransheine Rumtutuly (Fakultas Teknik Universitas Cenderawasih, 2023)
Klis Village is one of the villages located in Moa sub-district, MBD Regency. The daily activities of the people of Klis Village are farming, almost all the residents of this village earn their living by farming. One of the natural resources in Klis Village is cassava, or also known as cassava or cassava, which is an important food source in many tropical countries, including Indonesia. Cassava has great potential to be processed into various food products, one of which is crackers. Cassava crackers are a type of snack that is popular and has high demand among the public. Around 65% of the production of cassava chips (wet tubers) is used for human food as a main food such as a substitute for rice and a daily snack. Processing cassava into crackers can be an attractive alternative to improve the economy, especially in Klis village which has abundant cassava production. Seeing this potential, there is a need for creative and innovative efforts in processing cassava. Processing cassava into processed crackers is the solution offered in this community service program